Is peniaphobia an incentive to crime? - Siti Nur Zahara, Hamzah; Lau, Evan (Taylor & Francis, 2011)
This article analysed the relationship between crime categories and unemployment rates using a set of panel data for 14 states in Malaysia with data spanning from 1982 to 2008. It is well documented that crime and unemployment are negatively related in Malaysia; the same is the case for both violent and property crime. Increases in unemployment rates cause the consumption expenditure to decrease, especially among households, hence, causing potential earnings from illegitimate activities to drop and discouraging a person from committing a crime. However, the significant properties of the t-statistics indicate that it is important to consider the labour market conditions in employing appropriate policies in fighting crime. That being said, unemployment can indirectly explain hunger, poverty, decreasing standards of life and economic downturn.